Optimizing Halal Product Development Through Understanding Sharia Principles - Enceng Iip Syaripudin Enceng; Ujang Burhanudin; Amany; Deni Kon kon Furkony (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This study aims to analyze the role of understanding sharia principles in optimizing the development of halal products. The sharia principles in question include the prohibition of usury, gharar, and maisir, as well as the concepts of halal and haram in Islam. The research method used is a qualitative approach with case studies on companies engaged in the halal product industry. Data was collected through in-depth interviews with management, field observations, and review of company documents. Data analysis was carried out in a descriptive-interpretive manner. The results of the study show that a comprehensive understanding of sharia principles plays a key role in optimizing the development of halal products. This is reflected in the process of selecting raw materials, product formulation, packaging design, and marketing strategies that are in line with Islamic values. The development of halal products based on sharia compliance has been proven to increase consumer confidence, product differentiation, and company competitiveness in the market. The managerial implication of this study is the need to strengthen the competence of human resources in understanding and implementing sharia principles at every stage of halal product development. This is an important foundation for the company to achieve sustainable success in the halal industry.